Characteristics of an Advective Marine Heatwave in the Middle Atlantic Bight in Early 2017 - Gawarkiewicz, Glen; Chen, Ke; Forsyth, Jacob; Bahr, Frank; Mercer, Anna M.; Ellertson, Aubrey; Fratantoni, Paula; Seim, Harvey; Haines, Sara; Han, Lu (Frontiers in Marine Science, 2019)
There has been wide interest in marine heatwaves and their ecological consequences in recent years. Most analyses have focused on remotely sensed sea surface temperature data due to the temporal and spatial coverage it provides in order to establish the presence and duration of heatwaves. Using hydrographic data from a variety of sources, we show that an advective Marine Heatwave was initiated by an extreme shelfbreak exchange event in late December 2016 south of New England, with temperature anomalies measuring up to 6°C and salinity anomalies exceeding 1 PSU. Similar features were observed off of New Jersey in February 2017, and are associated with the Shelfbreak Front migrating from its normal position to mid-shelf or further onshore. Shelf water of 34 PSU was observed just north of Cape Hatteras at the 30 m isobath and across the continental shelf in late April 2017. These observations reveal that the 2017 Marine Heatwave was associated with a strong positive salinity anomaly, that its total duration was approximately 4 months, and its advective path extended roughly 900 km along the length of the continental shelf in the Middle Atlantic Bight. The origin of this Marine Heatwave is likely related to the presence of Warm Core Rings adjacent to the shelfbreak south of New England.